Get Well Soon Card: Self Help Program to Overcome Hospital Based Financial Barrier - Gajuryal, Sharad Hari; Satyal, Narayan; Bidari, Sangita; Panta, Shristi; Pant, Basant (Journal of Karnali Academy of Health Sciences, 2020)
Background: The health care cost is increasing not only in developed countries but also in developing countries. Although the modality of treatment has made significant progresses over the years, delivery of treatment is sometimes beyond the expectation of patient as well as inaccessible financially. Citizen from developing countries like Nepal have to pay out of their own pocket for even minor health issues. We initiated a new concept to bridge this gap between treatments and necessity of funds through crowd funding scheme.Methods: This was a cross sectional prospective and observational study conducted at Annapurna Neurological Institute and Allied Sciences from July 2017 to April 2020. This study was conducted on “Get Well Soon “card which was a friendly gesture with monetary value provided by visitors to patients. This card was made available in hospital pharmacy without any hidden cost. A convenient sample survey on 100 participant including admitted patients as well as visitors in the hospital was conducted on their perception about Get well soon card before initiating this program.Results: This innovative self-help scheme has been proven to be quiet successful in a short period of time with many supporters advocating in its favor. Total number of 1012 patients have been benefited from the card which was provided to them by their visitors and relatives during their hospitalization with purchase of card worth NRs. 1144500 (~$11445) during the study period. Conclusion: Get Well Soon Card can be beneficial to those populations who are financially constrained and lack insurance for the treatment. This Cultural Revolution of crowd funding can be duplicated not only in Nepal, but also in different developing countries where out of pocket system is still prevailing.